Students’ Perceptions on the Effectiveness Use of YouTube in Learning English - Rajagukguk, Dewi Veranita; Irma J.E , Janis; Anacy, Fidratan (JLE: Journal of Literate of English Education Study Program, 2025)
This study investigates how YouTube functions as an effective medium for English language learning among junior high school students at SMP Negeri Anggori by employing Classroom Action Research that integrates qualitative and quantitative approaches. Data were collected through tests, questionnaires, and interviews to evaluate learning outcomes and students’ attitudes toward the use of YouTube in learning. The results show significant improvements in students’ English proficiency and learning motivation, as reflected in the consistent increase in students’ scores from pre-test to post-test across each cycle, namely from 50.00 to 70.00 in Cycle 1, from 60.00 to 80.00 in Cycle 2, and from 50.10 to 75.30 in Cycle 3. These findings confirm that YouTube contributes positively and effectively as a medium for English learning, although some challenges in the form of distractions remain, highlighting the need for guided use and teacher supervision when integrating digital media into classroom activities.